Narrative analysis of the Presidential Convention Films of the U.S 2004 elections. - Cheong, Hao Zin. (2008)
This study examines the campaign biographical films of the two presidential candidates George W. Bush and John Kerry presented at the 2004 Republican and Democratic Party conventions. Using Walter Fisher’s Narrative Paradigm to analyze the respective films, the Bush film generally possessed the stronger narrative due to its narrow, streamlined approach, whereas the Kerry film appeared to be undermined by the presence of a number of elements which detracted from the overall coherence of the film.